ANALISIS ANTRIAN PADA PELAYANAN ALAT RTG DI LAPANGAN PENUMPUKAN TERMINAL BERLIAN (PT BERLIAN JASA TERMINAL INDONESIA) - Rachmah Agus Triati; Henita Rahmayanti (LOGISTIK, 2020)
This final task report aims to determine the model of the container queue at the diamond Terminal, as well as the graduation requirement of the Jakarta State University management course. From the calculation results of the system performance of the queue in the field of stacking the diamond terminal shows that the busiest month occurred in May with the number of containers arrival as much as 8199 boxes and the arrival of the most deserted containers occurred in the month June with a number of containers as much as 5332 boxes. The probability calculation results are not contained in the system queuing occurring in February and may by 0%. It shows the busyness of the RTG tool reaches 100% and the percentage of the most small bustle of the RTG tool in April and June by 20% showing the most lonely conditions in the queue system in the field of diamond buildup. The high level of arrival of containers in addition to the complexity of the diamond buildup field that eventually exceeded the capacity limit of the RTG tool thus giving rise to an imbalance between the arrival rate and the service level of the diamond terminal.